Bad-faith cooperation. Issue 4 (3rd July 2020) - Spaniel, William; Poznansky, Michael
ABSTRACT: In many political contexts, antagonistic actors face a tradeoff. Broadly, they profit from noncooperative actions. But taking those actions signals unfriendly preferences to their targets, who may then take proactive countermeasures to mitigate the damage of later defections. We develop a model to investigate how actors can manipulate the signaling incentives. We show that the target best avoids initial defections when the cost and effectiveness of countermeasures fall in a middle region. Although antagonists find misrepresentation profitable, the initial cooperation that uncertainty induces gives impatient targets a greater overall payoff than with complete information. As a result, impatient targets may want to pre-commit to less attractive countermeasures to enjoy the benefits of initial cooperation. We illustrate the mechanism with a case study of the Soviet and American policy toward Central-Eastern Europe at the end of the Cold War.